The analogy of grace: Karl Barth's moral theology - McKenny, Gerald P. (Oxford University Press, 2010)
A comprehensive treatment of Karl Barth's ethics, offering a thorough account of the development of Barth's ethical thought and a wide-ranging analysis of its chief concepts and arguments. McKenny explores the ways in which Barth's position engages the traditions of Christian ethics and modern continental moral thought